Smartphone Usage and Academic Performance of Management Science Students in an Emerging Economy - Friday Ogbu Edeh; Blessing Friday Edeh; Collins Irem Okechukwu; Mundu Mustafa; Ainebyoona Christine; Dayo Benedict Olanipekun; Neji Desmond Oben; Lilian Asinai; Najjuma Aisha (AIBPM Publisher, 2024)
Smartphone usage among students in tertiary institutions, particularly management sciences students, has generated concerns due to its potential negative effects on their academic performance and overall well-being. While smartphones are known to improve students' academic outcomes, their excessive use can lead to distractions and a decline in academic achievement, especially in developing economies. This study investigates the impact of smartphone usage on the academic performance of students in selected universities in southeast Nigeria. A cross-sectional survey was conducted among 300-level management science students at three public universities, with data collected through 221 valid questionnaires. The study found that students' academic performance is positively influenced by the perceived ease of use, usefulness, and enjoyment of smartphones. However, excessive use, particularly for non-academic purposes, negatively affects performance by causing distractions, addiction, and superficial learning. This study concludes that while smartphones can be a valuable academic tool, excessive usage for non-academic activities can hinder students’ academic performance. Effective management of smartphone use is essential for academic success.